Probing Key Concepts of Medically assisted death. Analyzing the Portuguese Constitutional Court’s Rulings - Cordeiro-Rodrigues, Luís; Wareham, Christopher Simon; Cruz Ribeiro, João (Acta Bioethica, 2025)
From 2021, the Portuguese parliament tried to get four versions of a law on medically assisted death approved. Two were rejected by the Portuguese Constitutional Court (PCC) because they were unconstitutional, and the President politically vetoed another. Finally, the parliament passed the law in 2023, even though the President and the PCC seem to oppose it. In this article, we analyze the PCC’s rulings on the medically assisted death law and contend that, broadly speaking, the PCC’s decisions to reject the law were justified. We focus on two core questions that have been critical in this debate: the meaning of ‘suffering’ and of ‘permanent injury of extreme gravity’. Further, we point to possible directions whereby the legislators may revise the law and thus solve the problems raised by the PCC.